2005
DOI: 10.1097/01202412-200501000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a malunited, isolated fracture of the capitate in a 6-year-old boy

Abstract: A 6-year-old boy with an isolated fracture of the capitate was presented. First radiograghs at our clinic revealed an oblique fracture with a displacement of 5 mm on the lateral view, which we successfully treated with immobilization. When complete union was recognized in the radiographs, the capitate had a deformity consisting of a large prominence on the palmar aspect. During follow-up, the capitate showed marked remodeling and at four and a half years after injury it had regained an almost normal shape. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
1
0
5
Order By: Relevance
“…Existe poca bibliografía relacionada con las fracturas aisladas del hueso grande en niños; encontramos un total de 38 casos descritos hasta la fecha, 3,7,8 los más frecuentes son los casos asociados a fracturas de escafoides 9 o a múltiples fracturas del carpo. 10 El mecanismo de lesión principal ocurre por traumatismo directo y, aunque la localización puede ser variable, en general, estas fracturas pueden clasificarse en tres grupos según describen, de forma gráfica, Kadar y cols.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Existe poca bibliografía relacionada con las fracturas aisladas del hueso grande en niños; encontramos un total de 38 casos descritos hasta la fecha, 3,7,8 los más frecuentes son los casos asociados a fracturas de escafoides 9 o a múltiples fracturas del carpo. 10 El mecanismo de lesión principal ocurre por traumatismo directo y, aunque la localización puede ser variable, en general, estas fracturas pueden clasificarse en tres grupos según describen, de forma gráfica, Kadar y cols.…”
Section: Discussionunclassified
“…Asimismo, en niños que todavía tienen inmadurez ósea, se torna dificultoso descartar otras lesiones del carpo. Por ello, es recomendable efectuar una resonancia magnética, 7,8 teniendo en cuenta que, en niños de corta edad, se requiere sedación o anestesia para mantener la extremidad inmovilizada. La resonancia debe incluir imágenes coronales en secuencia T1 para evaluar las relaciones anatómicas y la localización de la fractura y cortes coronales en secuencia STIR para analizar el edema de la médula ósea.…”
Section: Discussionunclassified
“…Isolated capitate fractures in skeletally immature patients are rare, with literature consisting only of a series of case reports (Klitscher et al, 2010; Kuniyoshi et al, 2005; Young, 1986). Minami et al (1987) reported a capitate nonunion in a 13-year-old girl.…”
mentioning
confidence: 99%
“…der Hals des Os capitatum [14] . In den meisten F ä llen verl ä uft die Fraktur transversal, seltener schr ä g [5] . Initial sollten R ö ntgenaufnahmen im dorso-palmaren und seitlichen Strahlengang angefertigt werden [14] .…”
unclassified
“…Initial sollten R ö ntgenaufnahmen im dorso-palmaren und seitlichen Strahlengang angefertigt werden [14] . Nicht selten jedoch stellen sich Kapitatumfrakturen in den Standardr ö ntgenaufnahmen prim ä r nicht dar oder werden ü bersehen [3,5,6,15] Das Os capitatum wird weitestgehend von ü ber im mittleren Kapitatumbereich einstrahlende palmare Gef ä ß e versorgt. Die Blutversorgung des proximalen Kapitatumpols erfolgt retrograd ü ber die Kapitatumtaille [17] .…”
unclassified